Peningkatan Kepatuhan Regulasi Melalui Pengembangan Sistem Informasi Keuangan Bagi Badan Usaha Milik Desa Menggunakan Teknologi Berbasis Website - Zamzami, Faiz; Aghadiati Fajri, Faridiah; Huda, Irkham; Prasetya Timur, Rudi (Akmenika: Jurnal Akuntansi dan Manajemen, 2024)
This study highlights the inability of village-owned enterprises (BUMDesa) to prepare financial reports according to guidelines, indicating a lack of financial accountability. Researchers attempted to develop a web-based platform to generate BUMDesa financial reports following Ministerial Decree Number 136 of 2022. We focus on the perspective of public sector accounting and accounting information systems to respond to research questions. Furthermore, application development considers the research and development (R&D) method and design science via the software development life cycle stages. A total of six BUMDesa contributed to developing this application. The result is a web-based financial reporting application platform that meets these criteria and guidelines. We also provide a platform usage procedure to facilitate its operation. The contribution of this study is to develop a financial information management platform for BUMDesa that emphasizes reporting accuracy and compliance.